A Valuable Endoscopic Tattooing Method for Early Gastric Cancer Localization before Laparoscopic Surgery - Wang, Sheng-Fu; Wu, Chi-Huan; Hsu, Jun-Te; Lee, Mu-Hsien; Lin, Cheng-Hui; Yeh, Ta-Sen; Lin, Chun-Jung; Sung, Kai-Feng (Archives of Clinical and Biomedical Research, 2022)
Background and Aims: Laparoscopic surgery for gastric cancer has become popular in recent years and preoperative localization is required as surgeons are unable to identify small tumors through tactile sensation during the surgery. Thus we would like to evaluate our novel endoscopic method using tattooing with SPOT for early gastric cancer localization preoperatively. Methods: 78 patients had tattooing with SPOT, with or without metal clip. We categorized these patients into two groups according to whether metal clips were used, and analyzed patients’ characteristics, pathological features and surgical outcomes. Furthermore, we classified patients into whether they underwent subtotal gastrectomy or pylorus-preserving segmentectomy and analyzed if our tattooing method could be feasible in both types of surgeries. We also evaluated the risk factors of insufficient safety margins to improve our tattooing method in the future. Results: 78 patients underwent endoscopic tattooing and 15 patients combined with metal clips. The patients’ characteristics, pathological features and surgical outcomes had no clinical significance between two groups. Additionally, subtotal gastrectomy and pylorus-preserving segmentectomy with preoperatively tattooing had similar outcomes except the duration of surgery is significantly shorter in the later. The analysis for risk factors of insufficient safety margin showed that only tumor size in specimens, especially above 2 cm, had clinical significance. Conclusions: Our method is feasible even without metal clips used and we suggest the location of tattooing or resection margin should be modified if the tumor size is more than 2 cm due to a higher rate of insufficient safety margin.